An Examination of the Relationship Between Levels of Food Security and Depression - (:unkn) unknown (My University, 2014)
Prior research has identified a variety of common correlates between food security and depression but oftentimes the data used in these analyses are not representative of the US or do not consider multiple categorical levels of the focal variables. Using data from the 2009-2010 National Health and Nutrition Examination (NHANES), this study sought to examine the relationship between four levels of food security - full, marginal, low and very low - and depression. The findings indicate low and very low food security are significantly related to an increased risk of depression, while marginal food security is not significantly different from full food security. Inclusion of interaction effects between food security and gender as well as food security and having a child/children were not found to be a significant improvement to the model.
Keywords: Anxiety; Comorbidity; Depression; Food Security; Gender; Parental Status